The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2022
DOI: 10.15587/1729-4061.2022.252549
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of employer brand for young people

Abstract: Different approaches to determining the employer brand were analyzed. The main components of the employer brand were identified. It is customary to divide the components of the employer brand into tangible and intangible ones. Material ones include wages, official employment, the material system of motivation. Intangible components are additional benefits, office, rating, and reputation of a company, type of activity of a company, the possibility of training and development. A tendency of the lack of informati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…It was evident that Generation Z demonstrates a prioritisation of workplace wellbeing and employee satisfaction. Factors such as salary level, employer-provided training, flexibility and leisure time, and opportunities for personal and professional growth within the organisation were deemed important by this cohort (Anggraeni 2022;Dzhulai et al 2022;Garai-Fodor and Jackel 2022;M. Islamiaty et al 2022;Kunal et al 2022;Lukić-Nikolić and Lazarević 2022).…”
Section: Content Analysismentioning
confidence: 86%
See 2 more Smart Citations
“…It was evident that Generation Z demonstrates a prioritisation of workplace wellbeing and employee satisfaction. Factors such as salary level, employer-provided training, flexibility and leisure time, and opportunities for personal and professional growth within the organisation were deemed important by this cohort (Anggraeni 2022;Dzhulai et al 2022;Garai-Fodor and Jackel 2022;M. Islamiaty et al 2022;Kunal et al 2022;Lukić-Nikolić and Lazarević 2022).…”
Section: Content Analysismentioning
confidence: 86%
“…According to RQ3, this systematic investigation also uncovered that the majority of studies retain an exploratory nature, frequently utilising methods to assess and substantiate simple and less robust hypotheses (e.g., Dzhulai et al 2022;Garai-Fodor and Jackel 2022;Kunal et al 2022;Samoliuk et al 2022). Furthermore, it was observed that a substantial number of these studies are conducted and published in university-affiliated journals (e.g., the studies by Jackel and Garai-Fodor 2022;Lukić-Nikolić and Lazarević 2022;and Wawer 2022).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation